Chapter La città e il vulcano. Il comune di Como e le conseguenze dell'eruzione del Samalas (1257-1260) - GRILLO, PAOLO (Reti Medievali E-Book, 2021)
The essay examines some measures taken by the commune of Como between 1257 and 1260, relating to the maintenance of roads and rivers and the food supply of the city, reinterpreting them as timely and effective responses to the wave of bad weather caused throughout Europe by the eruption of the Indonesian volcano Samalas.